Upaya Pengendalian Pemanfaatan Ruang Berbasis Risiko Bencana Banjir di Kecamatan Samarinda Utara - Ghendika Rai Ayari; Yulia Asyiawati (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Samarinda City is included in the area that is prone to floods and is the most frequently hit by floods. North Samarinda District is the worst flood-prone area in Samarinda City. The causes of frequent flooding in North Samarinda District are high rain intensity, land conversion and damage to the Karang Mumus River area. The aim of the research is to formulate flood risk-based space utilization control in North Samarinda District. This research was conducted using a vulnerability approach and a threat approach with quantitative and spatial methods in the form of scoring analysis and map overlay. The results of the analysis found that the biggest deviation in the use of space in North Samarinda District in the flood disaster area was in the form of a spatial plan for the designation of protected areas into settlements covering an area of 90.17 Ha located in East Sempaja Village. The vulnerabilities and threats to floods in North Samarinda District are dominated by high vulnerabilities and threats. High vulnerability and deviations in the use of space that occur affect each other and cause high flood inundation heights. Meanwhile, the high threat of flooding is caused by deviations in the use of space in the upstream area of the Karang Mumus sub-watershed in the form of a plantation cultivation area into a mining area of 78.31 square meters. Ha. The impact of the flood disaster caused by this high vulnerability and threat has disrupted the social and economic activities of the community. Therefore, it is necessary to control spatial use for North Samarinda District in the form of restoring spatial functions based on spatial pattern plans and efforts to control spatial use in the upstream area of the Karang Mumus sub-watershed in the form of controlling legal and illegal mining activities. Abstrak. Kota Samarinda termasuk dalam daerah yang rawan bencana banjir dan yang paling sering dilanda terhadap bencana banjir. Kecamatan Samarinda Utara merupakan kawasan rawan bencana banjir terparah di Kota Samarinda. Penyebab banjir yang sering terjadi di Kecamatan Samarinda Utara adalah intensitas hujan yang tinggi, alih fungsi lahan dan rusaknya ruang Sungai Karang Mumus. Tujuan dari penelitian yaitu merumuskan pengendalian pemanfaatan ruang berbasis risiko bencana banjir di Kecamatan Samarinda Utara. Penelitian ini dilakukan menggunakan metode pendekatan kerentanan dan pendekatan ancaman dengan metode kuantitatif dan spasial berupa analisis skoring dan overlay peta. Hasil analisis didapatkan bahwa penyimpangan pemanfaatan ruang terbesar di Kecamatan Samarinda Utara pada kawasan bencana banjir yaitu berupa rencana pola ruang peruntukan kawasan lindung menjadi permukiman seluas 90,17 Ha yang terletak di Kelurahan Sempaja Timur. Adapun kerentanan dan ancaman bencana banjir di Kecamatan Samarinda Utara didominasi oleh kerentanan dan ancaman yang tinggi. Kerentanan yang tinggi dan penyimpangan pemanfaatan ruang yang terjadi saling mempengaruhi dan menyebabkan ketinggian genangan banjir yang cukup tinggi. Sedangkan ancaman bencana banjir yang tinggi disebabkan oleh penyimpangan pemanfaatan ruang di kawasan hulu sub DAS Karang Mumus berupa kawasan budidaya perkebunan menjadi pertambangan seluas 78,31. Ha. Dampak dari bencana banjir yang diakibatkan oleh kerentanan dan ancaman yang tinggi ini menyebabkan kegiatan kegiatan sosial dan ekonomi masyarakat terganggu. Maka dari itu perlu adanya upaya pengendalian pemanfaatan ruang untuk Kecamatan Samarinda Utara berupa pemulihan fungsi ruang berdasarkan rencana pola ruang dan upaya pengendalian pemanfaatan ruang di Kawasan hulu sub DAS Karang Mumus berupa penertiban kegiatan pertambangan legal dan illegal.